Effects of the COVID-19 lockdown on orthopaedic trauma: a multicentre study across Scotland - David R. W. MacDonald; David W. Neilly; Peter S. E. Davies; Christopher R. Crome; Bilal Jamal; Sarah L. Gill; Arpit C. Jariwala; Iain M. Stevenson; G. Patrick Ashcroft; SCORE authors (Bone & Joint Open, 2020)
Aims: The UK government declared a national lockdown on 23 March 2020 to reduce transmission of COVID-19. This study aims to identify the effect of lockdown on the rates, types, mechanisms, and mortality of musculoskeletal trauma across Scotland. Methods: Data for all musculoskeletal trauma requiring operative treatment were collected prospectively from five key orthopaedic units across Scotland during lockdown (23 March 2020 to 28 May 2020). This was compared with data for the same timeframe in 2019 and 2018. Data collected included all cases requiring surgery, injury type, mechanism of injury, and inpatient mortality. Results: A total of 1,315 patients received operative treatment from 23 March 2020 to 28 May 2020 compared with 1,791 in 2019 and 1,719 in 2018. The numbers of all injury types decreased, but the relative frequency of hip fractures increased (36.3% in 2020 vs 30.2% in 2019, p < 0.0001 and 30.7% in 2018, p < 0.0001). Significant increases were seen in the proportion of DIY-related injuries (3.1% in 2020 vs 1.7% in 2019, p = 0.012 and 1.6% in 2018, p < 0.005) and injuries caused by falls (65.6% in 2020 vs 62.6% in 2019, p = 0.082 and 61.9% in 2018, p = 0.047). Significant decreases were seen in the proportion of road traffic collisions (2.6% in 2020 vs 5.4% in 2019, p < 0.0001 and 4.2% in 2018, p = 0.016), occupational injuries (1.8% in 2020 vs 3.0% in 2019, p = 0.025 and 2.3% in 2018, p = 0.012) and infections (6.8% in 2020 vs 7.8% in 2019, p = 0.268 and 10.3% in 2018, p < 0.012). Cycling injuries increased (78 in 2020 vs 64 in 2019 vs 42 in 2018). A significant increase in the proportion of self-harm injuries was seen (1.7% in 2020 vs 1.1% in 2019, p = 0.185 and 0.5% in 2018, p < 0.0001). Mortality of trauma patients was significantly higher in 2020 (5.0%) than in 2019 (2.8%, p = 0.002) and 2018 (1.8%, p < 0.0001). Conclusion: The UK COVID-19 lockdown has resulted in a marked reduction in musculoskeletal trauma patients undergoing surgery in Scotland. There have been significant changes in types and mechanisms of injury and, concerningly, mortality of trauma patients has risen significantly.